Academic Mobility as “Brain Drain” Phenomenon of Modern Higher Education - Svyrydenko Denys (Studia Warmińskie, 2017)
The authors examined the challenges of “brain drain” in the context of implementing the ideas of academic mobility in the Ukrainian higher education area. The problem was examined from the point of view of two methodological positions: firstly, in the context of the global trend of globalization, it actualizes the problem globally; secondly, in the context of the contradictions of post-colonial (post-totalitarian, etc.) sociocultural landscape of Ukraine, which gives the problem under study a specific nature. The authors proposed a methodological tool for the further study of the problem of social capital loss as a result of the implementation of academic mobility programs.